Analisis Spasial Ekologikal Sumberdaya Lahan di Provinsi Daerah Istimewa Yogyakarta - Worosuprodjo, Suratman (Forum Geografi, 2007)
Land resources is an important geographical aspect related to landuse allocation for human living. Â The aim of this research is to study the spatial ecological analysis for land resources in related to landuse type in the Province ofYogyakarta Special Region, the approach used in the research is landscape analysis based on geomorphological mapping, topographic map at scale 1:100000. Land resources potential in the study area can be classified based on landscape such as volcanic landscape, fluvial landscape, marine and eolion landscape, karst landscape (Gunung Sewu), structural - denudational landscape (Balur Agung). Landuse can be alocated based on the landscape condition, and limitation. Land limitation such as slope steepness, soils, natural hazard, water resources in each landscape can be used as detrminant factors in the landuse plan.